KEPENTINGAN BELANDA MELAKUKAN PENYITAAN KAPAL INDIA TAHUN 2008-2011 - Sihol Sahat M L T; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research is a economic political study which describes the interest of Netherland seizure of Indian Ships. This research will focus on why Neherland seizure the India Ships. This study interesting because describe about generic drugs from India and intellectual property rights. India is the third largest country in the production of generic drugs. India can do that after they make some revolusionery in intellectual property law. IndiaThis is qualitative research which used descriptive methods, and collecting datas from some resources like books,journals, official publications and relevant websites. This paper used the mercantilism perspective and Business Competition Theory from Michael E. Porter. The object in this research is Netherlands an main actor in International Relations.The result of this research shows that The Dutch seizure Indian ships because the ship contained drugs that infringed the patents. The patent of the drug is still owned by a company in the Netherlands. The company make a request to Dutch government to seizure the drugs to protect their product in Amrica market. The Netherlands confiscated the law of protection against counterfeit goods applicable in the European Union. The law provides the authority for each country to seizure the ship transiting in the EU region.Keywords : Seizure, Intellectual Property Rights, Economic Politic, Patent